Akuntabilitas Berbasis Karma - Paranoan, Natalia; Totanan, Chalarce (Jurnal Ilmiah Akuntansi dan Bisnis, 2018)
The purpose of this study is to reveal the meaning of accountability in financial management at Pura Giri Natha Makassar. The research method using qualitative methods with interpretive paradigm that emphasizes deep understanding of the meaning of accountability by actors and society. The results of this study revealed that accountability is not merely to be accompanied by the documents sources, accountability is not demanding the fulfillment of accounting standard with the technology and modern accountability systems, the principle of k arma became the main stronghold of accountability, in which the actor's behavior is restricted by the Moksartam Jagat Dita principle. Keywords : Accountability, financial management, karma , moksartam jagat dita .